Don't ever look back [large type] : a mystery - Friedman, Daniel, 1981- (Friedman, Daniel, 1981- Buck Schatz series, 2014)
Happily leaving his hated retirement home to do a job as a favor for a friend, octogenarian Buck Schatz encounters more than he bargained for when everything about the case goes wrong.